Giant dwarf crocodiles from the Miocene of Kenya and crocodylid faunal dynamics in the late Cenozoic of East Africa. Issue 10 (8th June 2022) - Brochu, Christopher A.; de Celis, Ane; Adams, Amanda J.; Drumheller, Stephanie K.; Nestler, Jennifer H.; Benefit, Brenda R.; Grossman, Aryeh; Kirera, Francis; Lehmann, Thomas; Liutkus‐Pierce, Cynthia; Manthi, Fredrick K.; McCrossin, Monte L.; et al.
Abstract: We describe two new osteolaemine crocodylids from the Early and early Middle Miocene of Kenya: Kinyang mabokoensis tax. nov. (Maboko, 15 Ma) and Kinyang tchernovi tax. nov. (Karungu and Loperot, 18 Ma). Additional material referable to Kinyang is known from Chianda and Moruorot. The skull was broad and dorsoventrally deep, and the genus can be diagnosed based on the combined presence of a partial overbite, a subdivided fossa for the lateral collateral ligament on the surangular, and a maxilla with no more than 13 alveoli. Phylogenetic analyses based on morphological and combined morphological and molecular data support a referral of Kinyang to Osteolaeminae, and morphological data alone put the new taxon at the base of Euthecodontini. Some Kinyang maxillae preserve blind pits on the medial caviconchal recess wall. Kinyang co‐occurs with the osteolaemine Brochuchus at some localities, and together, they reinforce the phylogenetic disparity between early Neogene osteolaemine‐dominated faunas and faunas dominated by crocodylines beginning in the Late Miocene in the Kenya Rift. The causes of this turnover remain unclear, though changes in prevailing vegetation resulting from tectonic and climatic drivers may provide a partial explanation.